Complement alternative pathway activation associated with pulmonary hypertension in lupus nephritis patients. (August 2019) - Li, Q; Li, H; Shi, J; He, B; Yu, F
Pulmonary hypertension occurs in systemic lupus erythematosus (SLE) for several reasons, such as vasculopathy. Previous studies have indicated that the excessive activation of the complement alternative pathway might be involved in the pathogenesis of lupus nephritis, especially in the absence of factor H or its functional impairment. However, the clinical and pathological significance of the alternative complement activation in lupus nephritis patients with pulmonary hypertension remains elusive. The data on patients with pulmonary hypertension and non-pulmonary hypertension lupus nephritis were retrospectively analyzed in our centre. Major plasma levels of complement components were evaluated. The depositions of Bb, C3d and C5b-9 in the lung specimens of pulmonary hypertension combined with SLE patients were detected by immunofluorescence staining. Among 352 lupus nephritis cases, 24 were diagnosed with pulmonary hypertension and 328 with non-pulmonary hypertension. Higher levels of Bb and lower levels of factor H were detected in the pulmonary hypertension group in comparison with the negative group ( P = 0.049, P = 0.024, respectively). Pulmonary hypertension was a risk factor for renal outcome as deduced by the log-rank and Cox test for survival analysis. C3d, C5b-9 and Bb were found to be positive in lung specimens of lupus nephritis patients with pulmonary hypertension. We concluded that activation of the complement alternative pathway may be involved in the pathogenesis of pulmonary hypertension in lupus nephritis.